LINGUOCULTURAL ASPECT THE CATEGORY OF SPACE IN ENGLISH AND UZBEK (Zamonaviy dunyoda pedagogika va psixologiya, 2022)
Linguistic aspect of the category of space in English and Uzbek languages is devoted to consideration of linguistic and cognitive aspects. The selection of this specific problem as a research subject is due to the insufficient development of the cultural studies plan of the translation. Although translation studies emphasizes the need to take into account the influence of culture on translation, no serious theoretical research has been conducted in this direction so far.